Creation of a mobile application prototype for post hemodialysis monitoring (Research, Society and Development, 2024)
Hemodialysis (HD) is called a method that uses filtration, diffusion and ultrafiltration with the aim of removing toxins present in the bloodstream due to Chronic Kidney Disease (CKD) and Chronic Renal Failure (CRF). In this way, technologies assume a role of change, bringing scientific and technological knowledge to solve problems that arise in different care sectors. This innovation will directly influence the diagnoses, treatment and prognosis of the individuals involved, generating cost reduction, assistance from professionals and effectiveness of care. The present study aimed to build a prototype mobile application for monitoring patients in home care after hemodialysis. Therefore, the guiding research question is: How will a prototype mobile application enable continued monitoring of kidney patients? This application prototype was built based on reflection on the complications that affect the patient after hemodialysis at home, thus aiming to build a tool that would assist in the health-disease process. This prototype consists of 12 screens, divided between its functionalities, Login, Registration, Main Menu, Nearby Hospitals, 24-Hour Teleconsultation, My Medical Record, Vital Data, Help Desk.